2011
DOI: 10.1101/gad.2024411
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning p53 activity through C-terminal modification significantly contributes to HSC homeostasis and mouse radiosensitivity

Abstract: Cell cycle regulation in hematopoietic stem cells (HSCs) is tightly controlled during homeostasis and in response to extrinsic stress. p53, a well-known tumor suppressor and transducer of diverse stress signals, has been implicated in maintaining HSC quiescence and self-renewal. However, the mechanisms that control its activity in HSCs, and how p53 activity contributes to HSC cell cycle control, are poorly understood. Here, we use a genetically engineered mouse to show that p53 C-terminal modification is criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 51 publications
3
48
0
Order By: Relevance
“…The constitutive activation of P53 is harmful for the stemness of HSPCs (Liu et al, 2010;Wang et al, 2011), whereas HSPCs in the p53 mutant are relatively normal (Lotem and Sachs, 1993). Here, we found that the transcript of p53 was specifically increased in the CHT region of rpc9 mutants, mediating HSPC impairments, which is similar to two works reporting that HSPC defects in zebrafish embryos deficient in TopBP1 (topoisomerase II β binding protein 1, involved in DNA replication and DNA damage) or the ribosome protein Rpl11 could be rescued by knockdown of p53 (Danilova et al, 2011;Gao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The constitutive activation of P53 is harmful for the stemness of HSPCs (Liu et al, 2010;Wang et al, 2011), whereas HSPCs in the p53 mutant are relatively normal (Lotem and Sachs, 1993). Here, we found that the transcript of p53 was specifically increased in the CHT region of rpc9 mutants, mediating HSPC impairments, which is similar to two works reporting that HSPC defects in zebrafish embryos deficient in TopBP1 (topoisomerase II β binding protein 1, involved in DNA replication and DNA damage) or the ribosome protein Rpl11 could be rescued by knockdown of p53 (Danilova et al, 2011;Gao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Three recent papers address the issue of how both mouse and human hematopoietic stem and progenitor cells (HSPCs) respond to radiation-induced DD [57][58][59]. These studies indicate that hematopoietic cells can adopt different means of handling DD, depending on their differentiation stage.…”
Section: Opinionmentioning
confidence: 99%
“…Surprisingly, they also show that DD responses in mouse or human cells follow opposite routes and unravel a different role for p53 in the DD response of HSPCs. Mouse HSPCs (defined as lin À Sca1 + cKit + flk2 À ) have a unique cell intrinsic mechanism that ensures their survival following X-ray treatment and which involves the activation of p53 and its transcriptional target p21 and DNA repair [58,59]. By contrast, human cord blood HSPCs exhibit p53-dependent radiation-induced apoptosis.…”
Section: Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the data presented here, these studies allude to the limitations of cell culture based approaches and further stress the need for a more physiological model, such as a transgenic mouse, to study the role of the p53 CTD in vivo. In fact, whereas the C-terminal lysines post-translational modifications originally were shown to be dispensable during embryogenesis and did not significantly affect p53 activity in mouse embryonic fibroblasts (19,20), a recent report shows that these modifications contributes to hematopoietic stem cells homeostasis and confirms the tissue and condition-specific effects of the post-translationally modified C-terminal lysines in vivo (49).…”
Section: Discussionmentioning
confidence: 96%